EGFR inhibitors in NSCLC and the role of biomarkers for selection of patients - Hirsch, Fred (Henry Stewart Talks, 2009)
USAEGFR TKIs in 2nd /3rd line therapy, Phase II activity of EGFR TKIs in unselected NSCLC, BR.21 study design and overall survival, Forest plot of survival by subsets, Is there a survival advantage for male smokers with squamous-cell carcinoma?, Trials comparing Gefitinib to Docetaxel, SIGN trial, RECIST study, INTEREST study, EGFR inhibitors in first line therapy, Randomized Trials of CT+/- active targeted Rx, Maintenance of Gefitinib WJTOG 0203, Cetuximab in NSCLC, EGFR interacting molecules
Archived at 2016/06/22